ROAK FISHING AND ITS PROBABLE EFFECTS ON THE CAPTURE FISHERY OF RIVER YAMUNA IN AGRA DISTRICT - Wishard, S K (Indian Journal of Fisheries, 2011)
The total annual yield of the economically important fishes of Yamuna in Agra is estimated from the catch statistics collected from 1960 to 1968. Monthly and annual fluctuations in catches, changes in fishing mortality, year-class strength, and mean lengths are presented and discussed in relation to the fishing methods, especially that of erecting barriers across the river, locally called ’Roak’. The catch by this method alone, constituting 54-88% of the total annual catch, is responsible for the declining trends in the major carp fishery of the area. Management measures that may be adopted to offer